Tradition Pattern of Use and Management of Land and Water of the Tribe of Arunachal Pradesh - Duarah, D.K. (Journal of Soil and Water Conservation, 2022)
In the life and culture of the people of Arunachal Pradesh there two aspects have played a magnificient role. Rice, Maize, Millet etc. are being the staple food of the tribes and agriculture is the main stay of their livelihood. The different tribes of state are well versed with the proper utilization and perfect management of land and water available within the jurisdiction of habitation. In tradition, the shifting cultivation is practised to a great extent by the tribesmen and it is deeply associated in their cultural fabrics, as rites and ceremonies, fair and festivals etc are celebrated with different stages of agricultural operation. They have, however, accepted WRC, TRC etc and use of fertiliser and pesticides etc. and as per survey, permanent cultivation predominates over shifting cultivation. In agri-operation both man women have equally participated and enjoy the output too.